PEMBUATAN EKSTRAKSI KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) DAN MADU SEBAGAI SEDIAAN PELEMBAB BIBIR KERING (LIPBLAM) - Rini Junaidah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Lip balm is a cosmetic product applied to the lips. It moisturizes the lips to prevent them from drying out and chapping. Lip balm is typically used for lips that require protection, such as in low humidity or excessively cold temperatures, to prevent evaporation of water and the mucosal epithelial cells on the lips. Honey is a readily available, non-plant-based natural ingredient that has beneficial properties for skin health. Using honey in lip balm can provide additional benefits for lip health and beauty. Honey's antibacterial and anti-inflammatory properties can help protect lips from infection and inflammation. Furthermore, the moisture produced by honey can improve the condition of dry, chapped lips. One natural ingredient that can be used as an active ingredient in lip balm preparations is the peel of the red dragon fruit (Hylocereus lemairei). The peel of the red dragon fruit contains vitamins C, E, and A, as well as alkaloids, terpenoids, flavonoids, thiamine, niacin, pyridoxine, cobalamin, phenolics, carotenes, and phytoalbumin. Several studies have shown that red dragon fruit contains vitamin C.